Meaning - Richard, Mark (Blackwell Pub., 2003)
Meaning brings together some of the most significant philosophical work on linguistic representation and understanding, presenting canonical essays on core questions in the philosophy of language. This anthology includes classic articles by key figures such as Frege, Quine, Putnam, Kripke, and Davidson: and recent reactions to this work by philosophers including Mark Wilson, Scott Soames, James Higginbotham, and Frank Jackson. Topics discussed include analyticity: translational indeterminacy: theories of reference: meaning as use: the nature of linguistic competence: truth and meaning: and relations between semantics and metaphysics. An extensive introduction gives an overview and detailed critical evaluation of the seminal views and arguments represented in the anthology. Meaning is an ideal text for courses in philosophy of language and semantics